Shield-roof interaction in longwall panels : insights from field data and their application to ground control - Cheng, Jingyi (2019)
The shield-roof interaction as mining proceeds in longwall panels remains unclear, hindering the further increase of longwall productivity. To uncover the mechanisms of shield-roof interaction, using our self-developed Status of Shield and Roof IntelliSense (SSRI) system, we investigated the effects of idle time, retreating rate, setting pressure, yielding, and shearer’s cutting, as well as neighboring shields’ advance on the spatial-temporal evolution of leg pressure and leg closure of shields. Our results show that the shield-roof interaction is not only dependent on the shield capacity, but also collectively determined by the time-related factors, the geological condition, the setting pressure, yielding characteristics, and mining method. Understanding the shield-roof interaction in longwall panels enables us to apply the SSRI system for ground control in longwall coal mines. Early warning of severe roof weighting can be achieved by establishing a warning model based on the decision tree algorithm. Apart from this, we can also assess the working condition of yield valve and diagnose fluid leakage of shield cylinder using the SSRI system. Finally, we propose the research prospects on shield-roof interaction in longwall panels to achieve a more reasonable determination of shield capacity, prediction of roof fall and coal wall spalling, and self-adaptive control of the shield.